Defining remission in rheumatoid arthritis. (28th March 2012) - Felson, David
Abstract : Objective: Given the inconsistency of remission definitions in rheumatoid arthritis (RA) trials, the goal of this American College of Rheumatology/European League Against Rheumatism committee was to define remission. Methods: The committee instructed a working group that a new remission definition, among other requirements, needed to allow for little, if any, active clinical disease and to be defined using the core set of outcome measures for RA trials and that those in remission at one time needed to have a low risk of later worsening function or radiograph progression. Remission was to be defined using trial data for use in trials but needed to anticipate use in a practice setting. Results: The working group started by evaluating the thresholds for core set measures compatible with remission and determined that patient-reported outcomes contributed importantly to the ability of outcome assessment to distinguish more from less effective treatments. The group created a candidate group of remission definitions to test, including Boolean versions and widely used indexes. Testing how well these candidate definitions predicted later good outcomes, the group found that Disease Activity Score 28 thresholds for remission performed worse than Simplified Disease Activity Index/Clinical Disease Activity Index or Boolean versions. Also, persons with low Disease Activity Score 28 occasionally had high joint counts, which were incompatible with remission. The parent committee chose two definitions: one Boolean (patient had to have all of the following: tender joint count, swollen joint count ≤1, C reactive protein ≤1 mg/dl) and patient global assessment ≤1 (on a 0–10 scale) and one Simplified Disease Activity Index ≤3.3. Conclusion: The American College of Rheumatology/European League Against Rheumatism has promulgated two new similar definitions of remission for RA trials.